An American Planter : Stephen Duncan of Antebellum Natchez and New York - Brazy, Martha Jane, 1965- (Book collections on Project MUSE., 2006)
"According to Brazy, Duncan was a hybrid, not fully a southerner or a northerner. He was also, Brazy shows, a paradox. Although he put down deep roots in Natchez, his sphere of influence was national in scope. Although his wealth was greatly dependent on the slaves he owned, he predicted a clash over the issue of slave ownership nearly three decades before the onset of the Civil War." "Perhaps more than any other planter studied, Duncan contradicts historians' definition of the southern slaveholding aristocracy. By connecting and contrasting the networks of this elite planter and those he enslaved, Brazy provides new insights into the slaveocracy of antebellum America."--Jacket.